Perlindungan Hukum Kreditur Terhadap Debitur Dalam Perjanjian Kredit Dengan Jaminan Letter C - Pramita Putri, Dwiyana; Ginanjar Fitrianto, Mukhammad; Syavira Dewi, Cornellia; Laksamana Abrianto, Alexander Christian; Shania Gisella, Heidy (UNES Law Review, 2024)
This research examines the position of Letter C in the ownership of land rights and legal protection for creditors in credit agreements with Letter C collateral. The findings show that the use of Letter C as credit collateral has a high risk for creditors because it does not provide strong legal certainty. The process of registering land with Letter C at the National Land Agency also takes a long time, adding to the uncertainty for creditors. This research aims to provide recommendations on better legal protection for creditors who receive collateral in the form of uncertified land.